(untitled) (Advances in Applied Mathematics and Mechanics, 2019)
In the paper we consider some plane boundary value problems of asymmetric theory of elasticity for perforated domains. The domain is the square with holes arranged in the definite manner. The formulated problems are solved approximately by using the method of fundamental solutions is used.